Sex differences in job attribute preferences - Bigoness, William J. [Verfasser] (My University, 1988)
"This study investigated the job attribute preferences of male and female MBA candidates. Participants were drawn from 27 different MBA programmes in the United States. Factor analysis of the job attributes questionnaire revealed three primary job attribute dimensions: (1) professional growth; (2) work environment; and (3) salary. Contrary to most previous research, females were found to place a greater emphasis on the professional growth dimension than did males. Males, on the other hand, placed greater emphasis on salary considerations. No sex difference was found in participants' ratings of the work environment job attribute dimension. Consistent with earlier research, women were found to place more importance on the calibre of colleagues than did males. In general, both males and females rated job attributes concerning job content as more important than job attributes concerning job context. These results are discussed with respect to earlier research findings. Finally, the generalizability of these findings to other occupational groups is discussed and managerial implications presented." (author's abstract) ((en)) In der in den Vereinigten Staaten durchgeführten empirischen Untersuchung wird der Frage nachgegangen, welche Arbeitsplatzmerkmale jeweils von männlichen und weiblichen Wirtschaftsstudenten bevorzugt werden. Im Vordergrund standen dabei die drei Dimensionen: Unternehmensgrösse, Arbeitsumgebung und Gehalt. Während die befragten Frauen mehr Gewicht auf die Unternehmensgrösse legten, wurde von den befragten Männern das Gehalt stärker gewichtet. (IAB)
Geschlechtsspezifische Präferenzen in Bezug auf Arbeitsplatzmerkmale
Keywords: G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; G 2.3.2 Arbeits- & Beschäftigungsverhältnisse; T 4.6 Wirtschafts- und Rechtswissenschaften; Arbeitsplatznachfrage; Einflussfaktor; Arbeitsplatzangebot; Einkommen; Arbeitsumwelt; Geschlechtsspezifische Faktoren; Student; Wirtschaftswissenschaft; Quantitative Angaben